Cord Blood Ischemia-Modified Albumin Levels in Normal and Intrauterine Growth Restricted Pregnancies. (16th April 2008) - Iacovidou, Nicoletta; Briana, Despina D.; Boutsikou, Maria; Liosi, Sophia; Baka, Stavroula; Boutsikou, Theodora; Hassiakos, Demetrios; Malamitsi-Puchner, Ariadne
Abstract : Ischemia-modified albumin (IMA) is a sensitive biomarker of cardiac ischemia. Intrauterine growth restriction (IUGR) may imply fetal hypoxia, resulting in blood flow centralization in favour of vital organs (brain, heart, adrenals—''brain sparing effect''). Based on the latter, we hypothesized that cord blood IMA levels should not differ between IUGR and appropriate-for-gestational-age (AGA) full-term pregnancies. IMA was measured in blood samples from doubly-clamped umbilical cords of 110 AGA and 57 asymmetric IUGR pregnancies. No significant differences in IMA levels were documented between AGA and IUGR groups. IMA levels were elevated in cases of elective cesarean section ( P = .035), and offspring of multigravidas ( P = .021). In conclusion, ''brain sparing effect'' is possibly responsible for the lack of differences in cord blood IMA levels at term, between IUGR and AGA groups. Furthermore, higher oxidative stress could account for the elevated IMA levels in cases of elective cesarean section, and offspring of multigravidas.